Incidence, Risk Factors, and Outcome of Acute Kidney Injury in Neurocritical Care. (April 2020) - Büttner, Stefan; Stadler, Andrea; Mayer, Christoph; Patyna, Sammy; Betz, Christoph; Senft, Christian; Geiger, Helmut; Jung, Oliver; Finkelmeier, Fabian
Purpose: Acute kidney injury (AKI) is a severe complication in medical and surgical intensive care units accounting for a high morbidity and mortality. Incidence, risk factors, and prognostic impact of this deleterious condition are well established in this setting. Data concerning the neurocritically ill patients is scarce. Therefore, aim of this study was to determine the incidence of AKI and elucidate risk factors in this special population. Methods: Patients admitted to a specialized neurocritical care unit between 2005 and 2011 with a length of stay above 48 hours were analyzed retrospectively for incidence, cause, and outcome of AKI (AKI Network-stage ≥2). Results: The study population comprised 681 neurocritically ill patients from a mixed neurosurgical and neurological intensive care unit. The prevalence of chronic kidney disease (CKD) was 8.4% (57/681). Overall incidence of AKI was 11.6% with 36 (45.6%) patients developing dialysis-requiring AKI. Sepsis was the main cause of AKI in nearly 50% of patients. Acute kidney injury and renal replacement therapy are independent predictors of worse outcome (hazard ratio [HR]: 3.704; 95% confidence interval [CI]: 1.867-7.350; P < .001; and HR: 2.848; CI: 1.301-6.325; P = .009). Chronic kidney disease was the strongest independent risk factor (odds ratio: 12.473; CI: 5.944-26.172; P < .001), whereas surgical intervention or contrast agents were not associated with AKI. Conclusions: Acute kidney injury in neurocritical care has a high incidence and is a crucial risk factor for mortality independently of the underlying neurocritical condition. Sepsis is the main cause of AKI in this setting. Therefore, careful prevention of infectious complications and considering CKD in treatment decisions may lower the incidence of AKI and hereby improve outcome in neurocritical care.